PENGARUH MODEL PEMBELAJARAN TECHNOPRENEURSHIP TERHADAP KUALITAS LULUSAN SMK TEKNIK KONTRUKSI BANGUNAN - Almasa Bahira (ADISAM PUBLISHER, 2024)
The study aims to examine the impact of technopreneurship on the vocational high school (SMK) graduates of the building building building, focused in the context of removing unemployment from high school and opening employment opportunities. Technopreneurship, a concept that combines technology and entrepreneurship, is becoming increasingly important in the face of global change and industrial revolution 4.0. Research methods used are descriptive analyses and case studies to get results on the increasing quality of SMKS graduating at technopreneurship. Research indicates that technopreneurship offers new opportunities for SMK graduates to create jobs of their own and to expand their businesses. However, challenges such as ignorance and entrepreneurial skills, as well as access to resources and capital, are still insurmountable obstacles. The implications of this study are the importance of strengthening SMK entrepreneurial education and improving cooperation between schools, industry, and governments to support the development of technopreneurship among SMK graduates of the building engineering program.